(3GdUGaj aj JaSjQ GdbQBfs - (3GdcGTj Ch GdcGTGfj, GdajV, eMeO Hf eQJVi Hf eMehO, J (B1091(3g`s ((3eMeO Hf EHQGgje Hf MSfs)
(3ChdgG (B:s
(3GdMeO ddg GdPj CfRd Ydi YHOg GdcJGH, jYfj GdbQBf Yde Gddg YHGOg cja jMeOhfg Ydi CLd fYeg Ydjge GdPj gh SHH fLGJge(B. (3hde jLYd dg YhLG (B...s
(3BNQgG (B:s
(3jfJgj HJaSjQ ShQI GdfGS(B: (3bd CYhP HQH GdfGS(B... (3hSHb SHH fRhd GdShQI hKhGH JdGhJgG (B...s
(3JHUQI GdeDda (B:s
(3haj GSeg NdGa(B: (3eMSf Hf eQJVi, Ch eMSf Hf eMeO, Ch eMeO eMSfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B617s
(3GdCYdGe(B: (3L(B5(3, U(B290s
(3eYLe GdeDdajf(B: (3L(B3(3, U(B617s
Keywords: (3GdJaSjQ hYdhe GdbQBfs